Morphological and structural evolution of WS2 nanosheets irradiated with an electron beam. Issue 4 (11th December 2014) - Wang, Yuqing; Feng, Yi; Chen, Yangming; Mo, Fei; Qian, Gang; Yu, Dongbo; Wang, Yang; Zhang, Xuebin
Abstract : Movement of atoms and the radiation damage mechanism in irradiated WS2 nanosheets. Abstract : The morphological and structural evolution of WS2 nanosheets under electron irradiation is investigated using high-resolution transmission electron microscopy. During irradiation, the sulfur atoms that interacted with the electrons were sputtered first and the tungsten atoms began to sputter when the surrounding sulfur atoms had been sputtered. With an increasing irradiation time, the remaining tungsten atoms rearranged to form new structures. In addition, the damage to the WS2 nanosheets became more severe with increasing electron energies and irradiation times.